Optimization of law enforcement on copyright infringement - Zusron, Ali (2017)
Purpose - This inquiry considers the crime of copyright infringement and to explore optimization of law enforcement on copyright infringement to the community and could possibly lead to a paradigm shift towards a criminal-oriented law. Methodology - Retributive and utilitarian theories of punishment were used to prevent diminishing the copyright infringement. Although a major increase in criminal copyright legislation should lead to higher scale enforcement, the current reality is that criminal prosecution is lacking, leading to a criminal copyright gap between legislation and law enforcement.Findings - Enforcement actions can chill lawful use of copyrighted material and ultimately reduce the production of creative expression, thus undercutting the very goal the law was intended to achieve. Although copyright law is not crime-oriented, it is feared that enforcement of copyright infringement will become more substantial if the opponents of law enforcement are low.